2011
DOI: 10.1021/es200759v
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Charging and Discharging of Capacitor to Enhance the Electron Production of Bioelectrochemical Systems

Abstract: A bioelectrochemical system (BES) can be operated in both "microbial fuel cell" (MFC) and "microbial electrolysis cell" (MEC) modes, in which power is delivered and invested respectively. To enhance the electric current production, a BES was operated in MFC mode first and a capacitor was used to collect power from the system. Then the charged capacitor discharged electrons to the system itself, switching into MEC mode. This alternate charging and discharging (ACD) mode helped the system produce 22-32% higher a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…In this study, we investigated the energy extraction with different inductances, duty ratios, and switching frequencies to characterize how these parameters affect MFC energy output performance. The energy harvesting frequency or switching frequency of the power converter ranges from 100 to 5000 Hz, which means that our switching periods (10 msece200 msec) were orders of magnitude shorter than previous studies, which were in the range of hours [8], minutes [12] and seconds [9,10].…”
Section: Introductionmentioning
confidence: 79%
“…In this study, we investigated the energy extraction with different inductances, duty ratios, and switching frequencies to characterize how these parameters affect MFC energy output performance. The energy harvesting frequency or switching frequency of the power converter ranges from 100 to 5000 Hz, which means that our switching periods (10 msece200 msec) were orders of magnitude shorter than previous studies, which were in the range of hours [8], minutes [12] and seconds [9,10].…”
Section: Introductionmentioning
confidence: 79%
“…EECs consist of common electric elements. The internal resistance in MFCs has been described by many researchers using EIS [34,35]. In this study, the capacitances were calculated by fitting the MFC EIS data.…”
Section: Eis Data Analysismentioning
confidence: 99%
“…Till date, several EECs have been developed to suit a variety of MFCs [27][28][29][30][31]. A simulation of EEC R(QR)(QR) is reported to determine the internal resistance in upflow MFCs [19,26,32,33]. You et al [34] reported a simulation of EEC R(QR)(CR) to determine the internal resistance of MFCs.…”
Section: Introductionmentioning
confidence: 99%
“…You et al [34] reported a simulation of EEC R(QR)(CR) to determine the internal resistance of MFCs. The components of internal resistance of MFCs have been the focus of the aforementioned studies in recent years [32][33][34][35]. Equivalent circuit modelling and its experimental validation via EIS is well known in the literature for energy storage devices such as Lithium ion batteries [36,37] and MFCs [38,39].…”
Section: Introductionmentioning
confidence: 99%